2003
DOI: 10.1002/chin.200319066
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Temperature Syntheses of Thioketals from Enol Ethers and Carbonyl Compounds.

Abstract: Protection Protection O 0345 Low-Temperature Syntheses of Thioketals from Enol Ethers and Carbonyl Compounds. -Carbonyl compounds and enol ethers are converted into the corresponding thioketals using TmsOTf as a stoichiometric reagent. -(MARTEL, A.; CHEWCHANWUTTIWONG, S.; DUJARDIN*, G.; BROWN, E.; Tetrahedron Lett.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…These binding sites have the capacity to react with volatile compounds, forming irreversible chemical binding and reversible bonding. Martel et al . reported that thiol groups on the surface of proteins could react with ketones and transform into dithioketals.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…These binding sites have the capacity to react with volatile compounds, forming irreversible chemical binding and reversible bonding. Martel et al . reported that thiol groups on the surface of proteins could react with ketones and transform into dithioketals.…”
Section: Resultsmentioning
confidence: 99%
“…36 These binding sites have the capacity to react with volatile compounds, forming irreversible chemical binding and reversible bonding. Martel et al 9 wileyonlinelibrary.com/jsfa reported that thiol groups on the surface of proteins could react with ketones and transform into dithioketals. Moreover, Zaugg et al 37 suggested that Schiff base linkages could be formed by the reaction between carbonyl compounds and free amino groups of proteins.…”
Section: Effect Of Microwave Treatments On Adsorbed Capacity Of Ketonesmentioning
confidence: 99%
See 2 more Smart Citations